Police complaints and discipline: integrity, lesson learning, independence and accountability: some implications of the reforms under the Policing and Crime Act 2017 - Torrible, Clare (Policing and society, 2021)
The Policing and Crime Act 2017 (PACA) aims to promote integrity within policing via a reformed police complaints and discipline process that focuses on lesson learning. Integrity and lesson learning are virtuous aspirations, but this paper queries the degree to which the reforms deliver them. Importantly, the analysis here provides a novel contribution to debates about lesson learning within the police by distinguishing lesson learning directed towards street-level officers from the accountability of police professional standards departments (PSDs) for how that is delivered. Focusing on the latter and drawing on the findings of the Chapman Review and a detailed analysis of police complaints statistics, it concludes that true lesson learning (from which increased integrity within forces can develop) requires increased external scrutiny of PSDs. In contrast, the analysis demonstrates that the PACA significantly increases PSDs’ de facto autonomy over the police complaints and discipline process and incorporates a shift in how independent oversight of police complaints is conceived. The paper borrows from Valverde’s suggested analytical framework to probe the underlying logic of the reforms, considering also the techniques they employ and the scale at which they operate. This reveals that the lesson learning agenda reframes expressions by citizens of mistreatment at the hands of the police as data upon which future policy might be based. In doing so, far from working to improve integrity, it may instead be ushering in a concerning biopolitical conception of policing which has the potential to exacerbate the worst features of police operational culture.